Relevance of the NLRP3 Inflammasome in the Pathogenesis of Chronic Liver Disease - Wu, Xiaoqin; Dong, Lei; Lin, Xianhe; Li, Jun (Frontiers in Immunology, 2017)
Inflammation is a common characteristic of most chronic liver disease (CLD). Inflammasomes are multi-protein complexes that can sense and recognize various exogenous and endogenous danger signals, eventually activating IL-1β and IL-18. The sensor component of the inflammasome system is a nucleotide-binding oligomerization domain (NOD)-like receptors (NLRs). The NLRP3 (NLRs family pyrin domain containing 3) inflammasome has been involved in the initiation and progression of CLD. However, the molecular mechanisms by which it triggers liver inflammation and damage remain unclear. Here, we focus on recent advances on the potential role of NLRP3 inflammasome activation in the progression of CLD, including viral hepatitis, nonalcoholic steatohepatitis (NASH) and alcoholic liver disease (ALD), and in particular, its ability to alleviate liver inflammation in animal models. Additionally, we also discuss various pharmacological inhibitors identifying the NLRP3 inflammasome signaling cascade as novel therapeutic targets in the treatment of CLD. In summary, this review summarizes the relevance of the NLRP3 inflammasome in the initiation and progression of CLD, and provides critical target to suppress the development of CLD in clinical management.